Integrating System Dynamics and Action Research: Towards a Consideration of Normative Complexity; Comment on “Insights Gained From a Re-analysis of Five Improvement Cases in Healthcare Integrating System Dynamics Into Action Research” - Rik Wehrens; Lieke Oldenhof; Marjolijn Heerings; Violet Petit-Steeghs; Sander van Haperen; Roland Bal; Trisha Greenhalgh (International Journal of Health Policy and Management, 2023)
Holmström and co-authors argue for the value of integrating system dynamics into action research to deal with increasing complexity in healthcare. We argue that despite merits, the authors overlook the key aspect of normative complexity, which refers to the existence of multiple, often conflicting values that actors in healthcare systems have to pragmatically develop responses to in their daily practices. We argue that a better theoretical and empirical understanding of the multiplicity of values and how actors deal with value conflicts in daily practices can enrich discussions about complexity in healthcare. We introduce the alternative methodology of ‘value exnovation’ for action researchers to broaden the scope of system-based thinking and action research in healthcare.